Successful Endoscopic Dacryocystorhinostomy: What Factors Make Revision Surgery More Likely?. (2nd September 2014) - Liu, Zi Wei; Jayaraj, Samuel; Subak‐Sharpe, Ian
Abstract : Objectives: Endoscopic dacryocystorhinostomy (DCR) is indicated for treatment of nasolacrimal duct obstruction, which manifests as a watery eye. Endoscopic techniques have gained popularity in recent years compared to open DCR, which leaves a facial scar. Success rates have been reported to be between 65‐95%. We report the success rate of endoscopic DCR at our institution and analyze factors leading to revision surgery. Methods: This is a retrospective analysis of endoscopic DCR performed at a district general hospital between August 2010 and December 2013. We perform this as a day case procedure using a DCR burr and leave silastic stents in situ. We do not routinely use anti‐mitotic agents. We collected and analyzed demographic data (age, co‐morbidity, medications), technical notes, rate of symptom resolution at follow‐up, and need for revision surgery. Results: A total of 33 endoscopic DCRs were performed in this time period. The overall success rate (satisfactory resolution of symptoms at minimum 3 months follow up) was 76%. Rate of revision surgery was 15%. In 50% of cases scar tissue obstructing the DCR opening was the cause of surgical failure. Previous surgery (external DCR/punctoplasty) was not associated with a higher rate of endoscopic DCR failure ( P =. 616). Conclusions: Endoscopic DCR is a safe technique for treating nasolacrimal duct obstruction with local success rates of 76%. A common reason for failure is scar tissue obstructing the rhinostomy opening and greater attention is being given to surgical techniques that maintain wide patency of the opening, as this may reduce rates of failure.